DIDACTIC POSSIBILITIES OF MULTIMEDIA TASKS IN THE INTENSIVE USE OF INNOVATIVE TECHNOLOGIES IN 1ST-GRADE MOTHER TONGUE LESSONS (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This thesis analyzes the didactic possibilities of multimedia tasks in the intensive use of innovative technologies in 1st-grade mother tongue lessons. It highlights their role in visualizing educational content, increasing learners’ cognitive activity, and developing grammatical skills. The research findings demonstrate that multimedia tasks contribute to enhancing students’ independent learning activities and improving the effectiveness of knowledge acquisition.
Keywords: 1st grade, mother tongue education, innovative technologies, multimedia tasks, digital didactics, interactive learning, cognitive activity, grammatical skills, formative assessment, educational effectiveness